If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9b + 8b = 32 Combine like terms: -9b + 8b = -1b -1b = 32 Solving -1b = 32 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-1'. b = -32 Simplifying b = -32
| (p/4)-3p/8)=4 | | -4x+20=-4(1+4x) | | 1-64u^3=0 | | (9/4)-(3p/8)=4 | | Ax-5=6x-7 | | 3(p-1.5)=13 | | 3a+bc=9d | | 6h-7=4.8h+5 | | 5=2e^1+x | | 3(x-8)=-22-2x | | 2x/40=12/40 | | 2x+4(x-2)=-(2x-8) | | x^1/2=64^1/3 | | 9-3x=-5x+1 | | x^1/2=64^1/3 | | y=30x+7 | | y=30x+7 | | y=30x+7 | | 5•3/10 | | 1/2(x-21)=3(10-3)*9 | | c-2.45=3 | | 49=1/16x^2 | | -4(n+3)-4=-1n-1 | | 2/=5/25 | | -22+5n=-3+3(1-2n) | | -50=9+m | | -5(1+8a)=-85 | | d=1/16x^2 | | -6/5y=6 | | 4(n+3)=7+5n | | 4x+-4x=8x | | 13g+2= |